COLLABORATIVE GOVERNANCE DALAM KEBIJAKAN RUANG TERBUKA HIJAU PUBLIK DI KOTA MAGELANG - Anisa Eka Fitriyani; Retno Sunu Astut; Yuliana Kristanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
According to UU 26/2007 of Spatial Planning, the percentage of green open space in the city area is at least 30% of the total area of the city consisting of 20% public green open space and 10% private green open space. Until early 2021, the percentage of public green open space in Magelang City has only reached 16% of total area of Magelang City. This is because there are still limited human resources and finances. The government of Magelang City still dominates in the management of public green open space and doesn’ t empower other stakeholders. To accelerate the achievement of the target of public green open space in Magelang City need collaboration between government with private and civil society. The collaboration of them in the process of formulating, implementing, and evaluating public policies is known as collaborative governance. The objectives of this study are (1) to identify the stakeholders in the Public Green Open Space Policy in Magelang City, (2) to analyse the role of each stakeholders in the Public Green Open Space Policy in Magelang City, (3) to analyse Collaborative Governance in the Public Green Open Space Policy in Magelang City. In this study, the researcher used a qualitative descriptive approach with Collaborative Governance theory by Ansell and Gash. The result of this study indicate that (1) the stakeholders of Public Green Open Space in Magelang City are DPUPR, DLH, Bank Jateng, Bank Magelang, HK Mustika Gold, and civil society, (2) DPUPR has role as a policy maker and coordinator; DLH acts as implementer; private as facilitator; and civil society as users of Public Green Open Space, (3) collaborative governance in the Public Green Open Space in Magelang City has not gone well, collaboration between the government and the private is only carried out for a certain period of time and there is not sustainable collaboration.